Pengaruh Lingkungan Kerja, Fasilitas Kerja dan Beban Kerja Terhadap Kinerja Karyawan pada PT. Lembah Karet Padang - Henryanto Abaharis; Suchi Dwinanda (Institut Nalanda, 2023)
The purpose of this study was to examine the effect of work environment variables on employee performance at PT. Padang Rubber Valley. to test the effect of work facility variables on employee performance at PT. Lembah Karet Padang, to test the effect of workload variables on employee performance at PT. Padang Rubber Valley. Collecting data by distributing questionnaires to 75 respondents, by using test instrument test (validity test and reliability test), descriptive analysis, classic assumption test (normality test, multicollinearity test and heteroscedasticity test) multiple linear regression and t test, with the help of the SPSS application. The results of the study show that the work environment has a positive and significant effect on employee performance at PT. Lembah Karet Padang, work facilities have a positive and significant effect on employee performance employee performance at PT. Lembah Karet Padang, workload has a positive and significant effect on employee performance employee performance at PT. Lembah Karet Padang, which means that the first hypothesis is accepted and the second hypothesis is accepted and the third hypothesis is accepted.